Balocistān, tārīk̲h̲, muʻāsharat - Qaiṣrānī, Shāhīn (Lāhaur : Yū Em.Ṭī. Pres, 2017)
Historical study of Balochistān, Pakistan.
Includes bibliographical references (369-379).
In Urdu.
Keywords: Balochistān (Pakistan) -- History; Pakistan -- Balochistān.; History